Osmotic Stress Induces Expression of Choline Monooxygenase in Sugar Beet and Amaranth - Russell, Brenda L. (American Society of Plant Physiologists, 1998)
Choline monooxygenase (CMO) catalyzes the committing step in the synthesis of glycine betaine, an osmoprotectant accumulated by many plants in response to salinity and drought. To investigate how these stresses affect CMO expression, a spinach (Spinacia oleracea L., Chenopodiaceae) probe was used to isolate CMO cDNAs from sugar beet (Beta vulgaris L., Chenopodiaceae), a salt- and drought-tolerant crop. The deduced beet CMO amino acid sequence comprised a transit peptide and a 381-residue mature peptide that was 84% identical (97% similar) to that of spinach and that showed the same consensus motif for coordinating a Rieske-type [2Fe-2S] cluster. A mononuclear Fe-binding motif was also present. When water was withheld, leaf relative water content declined to 59% and the levels of CMO mRNA, protein, and enzyme activity rose 3- to 5-fold; rewatering reversed these changes. After gradual salinization (NaCl:CaCl(2) = 5.7:1, mol/mol), CMO mRNA, protein, and enzyme levels in leaves increased 3- to 7-fold at 400 mm salt, and returned to uninduced levels when salt was removed. Beet roots also expressed CMO, most strongly when salinized. Salt-inducible CMO mRNA, protein, and enzyme activity were readily detected in leaves of Amaranthus caudatus L. (Amaranthaceae). These data show that CMO most probably has a mononuclear Fe center, is inducibly expressed in roots as well as in leaves of Chenopodiaceae, and is not unique to this family.